Anti-diabetic effects of Centratherum anthelminticum seeds methanolic fraction on pancreatic cells, Î²-TC6 and its alleviating role in type 2 diabetic rats. - Arya, A.; Yeng Looi, C.; Chuen Cheah, S.; Mustafa, Mohd Rais; Ali Mohd, M. (2012)
Ethnopharmacological relevance: Seeds of Centratherum anthelminticum (Asteraceae) have been popularly used in Ayurvedic medicine to treat diabetes and skin disorders. Folk medicine from Rayalaseema (Andhra Pradesh, India) reported wide spread usage in diabetes. Aim of the study: To investigate the hypoglycemic properties and mechanism of the methanolic fraction of C. anthelminticum seeds (CAMFs) on mouse Î²-TC6 pancreatic cell line and streptozotocin (STZ)-induced diabetic rat models. Materials and Methods: We investigated the crude methanolic fraction of C. anthelminticum seeds (CAMFs) on Î²-TC6 cell line and confirmed its effects on type 1 and type 2 diabetic rats to understand its mechanism in managing diabetes mellitus. CAMFs were initially tested on Î²-TC6 cells for cytotoxicity, 2-NBDG glucose uptake, insulin secretion and glucose transporter (GLUT-1, 2 and 4) protein expression. Furthermore, streptozotocin (STZ)-induced type 1 diabetic and STZ-nicotinamide-induced type 2 diabetic rats were intraperitoneally (i.p) injected or administered orally with CAMFs daily for 28 days. The effect of CAMFs on blood glucose and insulin levels was subsequently evaluated. Results: In cell line studies, CAMFs showed non-cytotoxic effect on Î²-TC6 cell proliferation compared to untreated control cells at 50 Î¼g/ml. CAMFs increased glucose uptake and insulin secretion dose-dependently by up-regulating GLUT-2 and GLUT-4 expression in these cells. Further in vivo studies on streptozotocin induced diabetic rat models revealed that CAMFs significantly reduced hyperglycemia by augmenting insulin secretion in type 2 diabetic rats. However, CAMFs displayed less significant effects on type 1 diabetic rats. Conclusions: CAMFs demonstrated anti-diabetic potential on Î²-TC6 cells and type 2 diabetic rat model, plausibly through enhancing glucose uptake and insulin secretion.